Prosodic development in European Portuguese from childhood to adulthood - Filipe, Marisa G. (2017)
We describe the European Portuguese version of a test of prosodic abilities originally developed for English: the Profiling Elements of Prosody in Speech-Communication (Peppé & McCann, 2003). Using this test, we examined the development of several components of European Portuguese prosody between 5 and 20 years of age (N = 131). Results showed prosodic performance improving with age: 5-year-olds reach adultlike performance in the affective prosodic tasks; 7-year-olds mastered the ability to discriminate and produce short prosodic items, as well as the ability to understand question versus declarative intonation; 8-year-olds mastered the ability to discriminate long prosodic items; 9-year-olds mastered the ability to produce question versus declarative intonation, as well as the ability to identify focus; 10- to 11-year-olds mastered the ability to produce long prosodic items; 14- to 15-year-olds mastered the ability to comprehend and produce syntactically ambiguous utterances disambiguated by prosody; and 18- to 20-year-olds mastered the ability to produce focus. Cross-linguistic comparisons showed that linguistic form–meaning relations do not necessarily develop at the same pace across languages. Some prosodic contrasts are hard to achieve for younger Portuguese-speaking children, namely, the production of chunking and focus.